Association between the findings of metachronous secondary primary malignancies and the number of Lugol-voiding lesions. Issue 9 (12th February 2020) - Katada, Chikatoshi; Yokoyama, Tetsuji; Yano, Tomonori; Oda, Ichiro; Shimizu, Yuichi; Takemura, Kenichi; Koike, Tomoyuki; Takizawa, Kohei; Hirao, Motohiro; Okada, Hiroyuki; Nakayama, Norisuke; Kubota, Yutaro; et al.
Summary: This study was designed to evaluate the relation between dysplastic squamous epithelium in the esophageal mucosa and the development of metachronous secondary primary malignancies (mSPM) other than esophagus after endoscopic resection (ER) in patients with early esophageal squamous cell carcinoma (SCC). We studied 330 patients with early esophageal SCC who underwent ER as a post hoc analysis of a prospective multicenter cohort study (UMIN Clinical Trials Registry ID UMIN000001676). Lugol-voiding lesions (LVL) were graded into 3 categories (A = no lesion; B = 1 to 9 lesions; C ≥ 10 lesions). The following variables were studied: (i) the incidences of mSPM other than esophagus; (ii) the standardized incidence ratios (SIRs) of mSPM; (iii) the cumulative incidence and total number of mSPM other than esophagus; and (iv) predictors of mSPM other than esophagus on analysis with a multivariate Cox proportional-hazards model. After a median follow-up of 46.6 months, mSPM other than esophagus was diagnosed in a total of 73 patients (90 lesions). Among the 106 patients in group C, 37 patients had mSPM (51 lesions), including head and neck cancer in 14 patients (24 lesions) and gastric cancer in 12 patients (16 lesions). The SIR of mSPM was 3.61 in this study subjects. An increase in the LVL grade (A to B to C) was associated with a progressive increase in the cumulative incidence rate of mSPM other than esophagus ( P = 0.017 for A vs. C, P = 0.023 for B vs. C). An increase in the LVL grade (A to B to C) was also associated with a progressive increase in the total number of mSPM other than esophagus per 100 person-years (primary events, relative risk [RR] = 1.66 and 3.24 for grades B and C, respectively, vs. A, P = 0.002 for trend; all events, RR = 1.81 and 4.66 for grades B and C, respectively, vs. A, P < 0.0001 for trend). LVL grade C was a strong predictor of mSPM other than esophagus (RR = 3.41 for A vs. C). LVL grade may be a useful predictor of the risk of mSPM other than esophagus after ER in patients with early esophageal SCC.